2005
DOI: 10.1080/08958370590899460
|View full text |Cite
|
Sign up to set email alerts
|

Serum Clara-Cell Protein and β2-Microglobulin as Early Markers of Occupational Exposure to Nitric Oxides

Abstract: Biochemical effects of NOx on 60 workers (both genders) of nitric acid production were studied. The control group consisted of 61 nonexposed people employed elsewhere in the plant. Although the actual threshold limit valuetime weighted averages (TLV-TWA) were not exceeded in the specific conditions of our study, the subjects were exposed to NO2 and NO during several exposure episodes with peak maximal concentrations of 140 ppm and 515 ppm, respectively. Additional cross-week evaluation of several biochemical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Linear regression analysis (Table 5), eliminating the effects of respective confounding factors (e.g., age, tobacco smoking) shows that CC16 and Al-S correlation was very strong (p = 0.006). It should be noted that this close relation supports the opinion that both markers (Al-S and CC16) are related, at least in part, to the daily fluctuation as already observed in cross-week CC16 evaluation in blood of shipyard welders and workers of a chemical plant exposed to nitric oxide [21,22]. Thus, inhibition of Clara cell protein secretion in smelters heavily exposed to Al can probably enhance Al-S levels by suppressing anti-inflammatory effect in the respiratory tract.…”
Section: Ijomeh 2006;19(4)supporting
confidence: 58%
See 1 more Smart Citation
“…Linear regression analysis (Table 5), eliminating the effects of respective confounding factors (e.g., age, tobacco smoking) shows that CC16 and Al-S correlation was very strong (p = 0.006). It should be noted that this close relation supports the opinion that both markers (Al-S and CC16) are related, at least in part, to the daily fluctuation as already observed in cross-week CC16 evaluation in blood of shipyard welders and workers of a chemical plant exposed to nitric oxide [21,22]. Thus, inhibition of Clara cell protein secretion in smelters heavily exposed to Al can probably enhance Al-S levels by suppressing anti-inflammatory effect in the respiratory tract.…”
Section: Ijomeh 2006;19(4)supporting
confidence: 58%
“…As a cell-specific marker for non-ciliated bronchiolar epithelial cells, which play a part in immunomodulatory and/or anti-inflammatory processes, assessment of Clara cell protein in serum (CC16) was proposed by various authors [14][15][16][17]. Recent studies on humans and rats have shown that CC16 is a sensitive biomarker of respiratory epithelial injury in exposures to welder fumes, glutaraldehyde, nitric oxides, or Al foundry dusts [18][19][20][21][22][23]. Clara cell proteins are involved in the pathogenic mechanisms leading to fibrosis [15,24], chronic obstructive pulmonary disease (COPD) [25,26], and asthma in humans [27][28][29] and in murine asthma model [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, urinary metallothionein and Cd are markers of Cd exposure as well as proximal tubular injury, and identifying the critical levels to indicate the onset of injury has been problematic (Chen et al 2006b;Nakajima et al 2005;Shaikh and Tohyama 1984;Shaikh and Smith 1986;Shaikh et al 1990;Suwazono et al 2006). Moreover, the urinary excretion of proteins such as b 2 -microglobulin can be influenced by actions of toxicants on organs other than the kidney (Halatek et al 2005;Hantson et al 2008;Roels et al 1999). Most significantly, these markers only identify later stages of Cd-induced kidney injury.…”
Section: Novel Biomarkersmentioning
confidence: 95%
“…In addition, urinary levels of some markers may be influenced by toxic actions of Cd on organs other than the kidney. For example, as the invariant light-chain component of class I major histocompatibility antigens, b 2 microglobulin is derived from many tissues, and serum levels of the protein can be influenced by pathologic processes in a variety of organs (Broeckaert et al 2000;Halatek et al 2005;Kobryn et al 1989;Poulik et al 1979).While an argument can be made that this lack of organ specificity could actually be desirable for biomonitoring the effects of a substance, such as Cd, that can affect multiple organ systems, this same lack of organ specificity can greatly complicate the use of the biomarker for mechanistic studies. For these reasons, any interpretation of results with any biomarkers must include some reference to levels of Cd in blood, tissues and/or urine.…”
Section: Biomarker Caveats and Problemsmentioning
confidence: 99%
“…As a cell-specific marker for nonciliated bronchiolar epithelial Clara cells, which play a part in immunomodulatory and/or antiinflammatory processes, assessment of Clara cell protein in serum (CC16) was proposed by various authors [6,7]. Recent studies have shown that CC16 is a sensitive biomarker of respiratory epithelial injury in exposures of humans and animals to welder fumes [8], nitric oxides [9], glutaraldehyde [10], or low CC16 levels in serum were noted in active smokers [11,12] and in silicaexposed workers [13].…”
Section: Introductionmentioning
confidence: 99%